ANALYSIS OF POPULAR ARTIFICIAL INTELLIGENCE PROGRAMS IN EDUCATION: STUDENTS PREFERENCES - Kanatbekova, А.А.; Kemelbek, М.Н.; Bereke, М.Б.; Sheraliyeva, Р.А.; Yessirkep, С.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
In recent years, technologies of artificial intelligence (AI) have become an integral part of the educational process, providing students with new opportunities for training and self -realization. The popularity of AI programs among students is explained by their ability to simplify access to educational materials, automate routine tasks and personalize the learning process. This article presents an analysis of the most popular and tools such as ChatGPT, Grammarly, Quizlet, Canva and Duolingo, which are actively used by students to write essays, prepare for exams, learn foreign languages ​​and create multimedia content. The study reveals which programs are most often selected by students, their main functions, advantages and restrictions. The results of the work allow us to understand how AI programs affect the effectiveness of training, as well as outline the prospects of their further application in the educational environmen